Peran Indonesia dalam Penyelesaian Sengketa Hukum Internasional di Perbatasan Laut Natuna - Haris Kusumawardana; Agoes Djatmiko (Fakultas Hukum Universitas Boyolali, 2023)
The issue of maritime boundaries is a fundamental matter that should be resolved and agreed upon by a country. The purpose of this research was to find out how the regulation of the law of the sea convention (UNCLOS 1982) relates to the settlement of maritime disputes between countries and how the authority of the international court of law of the sea (International Tribunal for The Law Of The Sea-ITLOS) in resolving maritime disputes. By using the method normative juridical research, qualitative methods and the concept of national interest, geopolitics and geostrategy are used to analyze this study. In this study, the South China Sea is the border for several countries, including Indonesia, Vietnam, Malaysia, Brunei, the Philippines and China. Because of this, border disputes in the South China Sea have quite high dynamics. This writing uses normative juridical research methods, with primary and secondary data to assist writers in finding research results and discussion. It is the obligation of Indonesia as a sovereign country to be able to play an active role in maintaining world peace in the form of participating in resolving disputes on the border of the Natuna Sea.